A retrospective study on the clinical efficacy of the intense pulsed light source for photodamage and skin rejuvenation. (18th May 2016) - Ping, Chen; Xueliang, Du; Yongxuan, Li; Lin, Deng; Bilai, Liu; Shaoming, Lin; Gold, Michael H.
Abstract : Objective: The objective of this retrospective review is to investigate the long-term effect of skin rejuvenation by the intense pulsed light (IPL) source for the treatment of photoaging.Methods: From 5300 clinical cases that our department has treated with the IPL, the first 2534 were chosen for this study. Each patient received a minimum of 3 IPL treatments during this time—many were yearly treatments. Clinical photographs were taken on a yearly basis for up to 12 years and sent to a blinded independent panel to study the effects of continuous IPL treatments.Results: Results showed that the effective rate for the IPL was between 88.24% and 96.45%.Conclusions: IPL therapy is an effective treatment for photoaging and can truly have an effect on reversing the signs of photodamage on skin.